Kemitraan Kementerian Agama Kota Batu dan PT Bank BNI Syariah Kota Batu dalam Inovasi Meningkatkan Pelayanan Administrasi Ibadah Haji - Indah Sari, Novi (Jurnal Ilmiah Administrasi Publik, 2018)
The process of administering haj pilgrimage services organized by the Ministry of Religious Affairs is faced with a process that is still not effective and efficient. In the process of Hajj registration, Calon Jemaah Haji (CJH) must go through four stages of the process performed in two different places. Sistem Tekhnologi dan Komputerisasi Haji Terpadu (SISKOHAT) had used as â€œjantungâ€ service, which in the process has always been innovated to correct the deficiencies. This study aims to describe and analyze the public response to the quality of services provided with partnerships established between the Ministry of Religious Affairs Batu City and PT Bank BNI Syariah Batu City. The quality of the Hajj service is better perceived by the community in the presence of established partnerships and new innovations created, but the partnership has not reached the joint service stage â€satu atapâ€.